Ageing in Place VS Panti Wreda: Menyatukan Dua Konsep yang Bertentangan - Ni Luh Putu Pradnyandari Kencana Putri; Made Diah Lestari (Faculty of Psychology Universitas Gadjah Mada, 2023)
As the population of older people grows, ageing issue becomes a priority to overcome in order to facilitate well-being among older people in Indonesia. One of critical factors that contributes to well-being is living arrangement. Ageing in place is a concept that refer to the ability of older people to live safely, independently, and comfortably in their homes as long as possible. However, there are some of older people and families who experience scare resources in caregiving and housing. To overcome these issues, institutional care is provided by the government to assist older people who do not have sufficient social supports. However, transferring older people from home to institutional care are still being a debate in Indonesia. In another words, institutional care is considered taboo by most Indonesians. In addition, international literatures emphasized the important of ageing in place and regard institutional care quite opposite to ageing in place. Therefore, this literature study aims to discuss the concept of ageing in place, institutional care, and to propose the idea to integrate the two conflicting concepts in order to facilitate inclusiveness among older people. This article is also expected to contribute to facilitate well-being among older people in Indonesia.